\(\dfrac{9^2.9^3.6}{3^{11}}\)

Tính

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 12 2021

\(=\dfrac{3^4\cdot3^6\cdot3\cdot2}{3^{11}}=2\)

25 tháng 12 2021

\(\dfrac{9^2.9^3.6}{3^{11}}=\dfrac{\left(3^2\right)^2.\left(3^2\right)^3.3.2}{3^{11}}=\dfrac{3^4.3^6.3.2}{3^{11}}=\dfrac{3^{11}.2}{3^{11}}=2\)

6 tháng 12 2017

a) \(\dfrac{1}{2}-\dfrac{3}{4}.\dfrac{-6}{5}\)

\(=\dfrac{1}{2}-\dfrac{3.\left(-6\right)}{4.5}\)

\(=\dfrac{1}{2}-\dfrac{-18}{20}\)

\(=\dfrac{1}{2}+\dfrac{9}{10}\)

\(=\dfrac{5}{10}+\dfrac{9}{10}\)

\(=\dfrac{5+9}{10}\)

\(=\dfrac{14}{10}\)

\(=\dfrac{7}{5}\)

b) \(\dfrac{\dfrac{1^0}{9}.3^2.9^3}{729}\)

\(=\dfrac{9^{-1}.3^2.9^3}{729}\)

\(=\dfrac{9^{-1}.9.9^3}{729}\)

\(=\dfrac{9^{-1+1+3}}{729}\)

\(=\dfrac{9^3}{729}\)

\(=\dfrac{729}{729}\)

\(=1\)

a: \(=\left(\dfrac{5}{15}-\dfrac{12}{9}\right)+\left(\dfrac{14}{15}+\dfrac{11}{25}\right)+\dfrac{2}{7}\)

\(=\left(\dfrac{1}{3}-\dfrac{4}{3}\right)+\dfrac{70+33}{75}+\dfrac{2}{7}\)

\(=-1+\dfrac{2}{7}+\dfrac{103}{75}=\dfrac{-5}{7}+\dfrac{103}{75}=\dfrac{346}{525}\)

b: \(4\cdot\left(-\dfrac{1}{2}\right)^3+\dfrac{1}{2}\)

\(=4\cdot\dfrac{-1}{8}+\dfrac{1}{2}=\dfrac{-1}{2}+\dfrac{1}{2}=0\)

c: \(\dfrac{10^3+5\cdot10^2+5^3}{6^3+3\cdot6^2+3^3}=\dfrac{5^3\cdot8+5\cdot5^2\cdot2^2+5^3}{3^3\cdot2^3+3\cdot2^2\cdot3^2+3^3}\)

\(=\dfrac{5^3\left(8+4+1\right)}{3^3\left(8+4+1\right)}=\dfrac{125}{27}\)

e: \(\dfrac{2^8\cdot9^2}{6^4\cdot8^2}=\dfrac{2^8\cdot3^4}{3^4\cdot2^4\cdot2^6}=\dfrac{1}{4}\)

14 tháng 12 2017

=9

14 tháng 12 2017

=9

19 tháng 6 2018

8)\(\frac{4}{9}:\left(-\frac{1}{7}\right)+6\frac{5}{9}:\left(-\frac{1}{7}\right)\)

=\(\frac{4}{9}:\left(-\frac{1}{7}\right)+\frac{59}{9}:\left(-\frac{1}{7}\right)\)

=\(\left(\frac{4}{9}+\frac{59}{9}\right).\left(-7\right)\)

=7.(-7)

=-49

9 tháng 11 2018

a.\(\dfrac{17}{15}\div\dfrac{4}{3}=\dfrac{17}{20}\)

b.\(\dfrac{-12}{21}\div\dfrac{34}{43}=\dfrac{-86}{119}\)

c.\(\dfrac{-5}{9}\times\dfrac{3}{11}+\dfrac{13}{18}\times\dfrac{3}{11}\)

=\(\dfrac{3}{11}\times(\dfrac{-5}{9}+\dfrac{13}{18})=\dfrac{3}{11}\times\dfrac{1}{6}=\dfrac{1}{22}\)

d.\(\dfrac{-2}{9}\times\dfrac{5}{11}+\dfrac{-16}{9}\times\dfrac{5}{11}=\dfrac{5}{11}\times(\dfrac{-2}{9}+\dfrac{-16}{9})\)

=\(\dfrac{5}{11}\times(-2)=\dfrac{-10}{11}\)

a: \(=2^2\cdot9\cdot\dfrac{1}{6\cdot9}\cdot\dfrac{4^2}{9^2}=\dfrac{2^2}{6}\cdot\dfrac{2^4}{3^4}=\dfrac{2^6}{2\cdot3\cdot3^4}=\dfrac{2^5}{3^5}=\left(\dfrac{2}{3}\right)^5\)

b: \(=2^8\cdot\dfrac{3^4}{2^4}=3^4\cdot2^4=6^4\)

c: \(=\dfrac{\left(\dfrac{1}{2}\right)^3\cdot2^3\cdot\left(\dfrac{1}{2}\right)^2}{\left(-8\right)^2\cdot16}\cdot2^6=\dfrac{\dfrac{1}{2^2}}{64\cdot16}\cdot64=\dfrac{1}{4}:16=\dfrac{1}{64}=\left(\dfrac{1}{8}\right)^2\)

a: \(=2^2\cdot9\cdot\dfrac{1}{3^3\cdot2}\cdot\dfrac{2^4}{3^4}=\dfrac{2^4\cdot2^2}{2}\cdot\dfrac{9}{3^3\cdot3^4}=\dfrac{2^5}{3^5}=\left(\dfrac{2}{3}\right)^5\)

b: \(=2^8\cdot\dfrac{3^4}{2^4}=3^4\cdot2^4=6^4\)

c: \(=\dfrac{\dfrac{1}{2^3}\cdot\dfrac{1}{2^2}\cdot8}{\left(-8\right)^2\cdot2^4}\cdot2^6=\dfrac{1}{2^2}\cdot2^6:2^{10}=\dfrac{2^4}{2^{10}}=\dfrac{1}{2^6}=\left(\dfrac{1}{8}\right)^2\)